2017
DOI: 10.1038/nature23015
|View full text |Cite|
|
Sign up to set email alerts
|

Cholangiocytes act as facultative liver stem cells during impaired hepatocyte regeneration

Abstract: SummaryFollowing liver injury, regeneration occurs through self-replication of hepatocytes. In severe liver injury, hepatocyte proliferation is impaired, a feature of human chronic liver disease1,2. It is contested whether other liver cell types can regenerate hepatocytes3–5. Here, we use two independent systems to impair hepatocyte proliferation during liver injury to evaluate the contribution of non-hepatocytes to parenchymal regeneration. Firstly, loss of β1-Integrin in hepatocytes with liver injury trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
444
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 442 publications
(467 citation statements)
references
References 28 publications
20
444
1
2
Order By: Relevance
“…To facilitate BEC‐driven repair, we next administered CDE diet to WT2 and KO2 mice for 2 weeks, followed by recovery on normal diet for 2 weeks (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate BEC‐driven repair, we next administered CDE diet to WT2 and KO2 mice for 2 weeks, followed by recovery on normal diet for 2 weeks (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…The role of BECs in mediating LR has remained controversial, as several studies have reported a limited role for BEC differentiation to hepatocytes . Recent studies have demonstrated that widespread hepatocyte senescence, hepatocyte ablation, impaired hepatocyte proliferation, or prolonged exposure to severe liver injury can trigger differentiation of BECs to hepatocytes. Interestingly, a previous study reported ductular reaction and BEC‐to‐hepatocyte differentiation in aged Albumin ‐Cre β‐catenin KO livers, suggesting expression of β‐catenin in hepatocytes is important for long‐term liver health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage tracing of duct cells to acinar cells was observed only under conditions of severe cell loss. The ability of lineage-restricted cells to either change phenotype or to generate other cell types to compensate for tissue loss is frequently recognized as a mechanism involved in regeneration (Raven et al, 2017; Thorel et al, 2010). Cellular plasticity is induced in several tissues as part of the normal injury response (Merrell and Stanger, 2016; Tata and Rajagopal, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transplantation of clonogenic LPCs into hepatocyte-senescent murine livers, induced through deletion of the E3 ubiquitin ligase Mdm2, resulted in restoration of the hepatic parenchyma through generation of hepatocytic or biliary epithelia (18). The exact underlying mechanisms of LPC-mediated liver regeneration are not always clear; however, hepatocyte senescence seems to be a definite histological requirement (19).…”
Section: Liver Progenitor Cells and Cancer Stem Cellsmentioning
confidence: 99%